Policy Handling Covid-19 and Effects of Pandemic on Workers in Palembang City - Bachtari Alam Hidayat; Putri Erlyn (Budapest International Research and Critics University, 2021)
Early in 2020 the world community was shocked by Covid-19 which has caused death rates to increase in various countries. The government has carried out various policies as an effort to prevent the transmission of Covid-19, one of which is by implementing Large-Scale Social Restrictions (PSBB), which is a localized lock down modification according to the level of severity in the Province, Regency or City. This research was conducted to determine the policies for handling Covid-19 and the unemployment rate due to the effects of the pandemic on workers in Palembang City. The Covid-19 pandemic not only caused health problems but also had an impact on policies taken by the central and local governments.